(untitled) (Medicine Today, 2020)
Introduction: Chronic obstructive pulmonary disease (COPD) is the fourth most common cause of death in the world and will become the third most common in a few years. Identification of prognostic factors may lead to improved treatment strategies and clinical outcomes for COPD. To find out the association between glucose levels and hospital outcomes in patients with acute exacerbations of chronic obstructive pulmonary disease. Materials and Methods: This retrospective study was carried out different privet and public hospital in Chandpur. The information reported in this manuscript was collected during three separate projects in the same hospital. The first cohort included 35 COPD patients admitted for an acute exacerbation to a non-ICU bed to determine if there was a relationship between corticosteroid dosage and hyperglycemia. The second cohort included 210 COPD patients with acute exacerbations who were admitted to the MICU to determine factors associated with mortality and LOS. The third cohort included 105 COPD patients who were monitored for re-admission within 30 days after discharge for an acute exacerbation. Results: Mean arterial pressure, hemoglobin, blood urea nitrogen, albumin, nursing home, pleural effusion and intubation were statistically significant (p<0.05) between two group. Intubation had 5.318 (95% CI 2.578 to 11.721) times increase in odds having length of stay. Intubation was significantly associated with length of stay. Conclusion: Mean arterial pressure, hemoglobin, blood urea nitrogen, albumin, nursing home, pleural effusion and intubation were statistically significant between in hospital deaths group and survivors group. Medicine Today 2020 Vol.32(1): 62-66